Marginalization Of Dalits And Bama’s Karukku (Journal of Namibian Studies : History Politics Culture, 2022)
Society may become marginalized for a variety of reasons. The main causes are caste, gender, and income. In terms of caste, a group of individuals may be stigmatized as untouchables. One such group is the Dalit community, whose members are marginalized by upper caste members and viewed as untouchables. Dalit literature is explicitly committed to social justice, social equality, and resistance to oppression, discrimination, and economic exploitation. It is either written by members of the Dalit communities or is specifically written to be the social, historical, and cultural aspects of the Dalit communities. As a teacher and, more importantly, as a writer, Bama has set up herself in academic circles, despite being a member of the first-generation student body in her community. She places a strong focus on education as a tool for empowering society. Many forms of brutal oppression meted out to Dalits, particularly to the Paraiyar caste, are discussed in Bama’s Karukku.